Eating problems in young children – a population‐based study. (27th November 2012) - Equit, Monika; Pälmke, Meike; Becker, Nicolas; Moritz, Anne‐Michaela; Becker, Sabine; von, Alexander
Abstract Aim To analyse the prevalence of atypical eating problems and their associations with anxious or oppositional behaviours in young children. Methods One thousand and ninety children examined in the school enrolment test in a defined geographical region were included (544 boys). The parents completed a 25‐item questionnaire regarding their child's eating behaviour and anxious or oppositional behaviours. Results Half of the parents reported that their child avoids certain foods (53%). Twenty‐three percent showed selective eating, 26% showed an aversion against new foods. Children with underweight avoided more types of food and ate smaller amounts than children with normal or overweight. Three groups could be differentiated. Sixty‐one percent of the children were 'normal eaters' with avoidance of certain foods, normal weight status and low anxious or oppositional behaviour. Thirty‐four percent showed selective and/or restrictive eating, and 5% worried about their weight. Children with selective eating and with weight concerns were more often affected by anxious and oppositional behaviours. Conclusion Atypical eating problems are common in young children. Without accompanying weight loss, behavioural or emotional problems, selective eating should be seen as a normal feature in young eating behaviour. Parents of young children with selective, restrictive eating or with weight worrying and psychological problems should be offered advice/treatment.